2023
DOI: 10.1186/s12964-023-01376-x
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the role of Niemann-pick C1 (NPC1) in viral infections and inhibition of viral infections through NPC1 inhibitor

Irfan Ahmad,
Seyede Narges Fatemi,
Mohammad Ghaheri
et al.

Abstract: Viruses communicate with their hosts through interactions with proteins, lipids, and carbohydrate moieties on the plasma membrane (PM), often resulting in viral absorption via receptor-mediated endocytosis. Many viruses cannot multiply unless the host’s cholesterol level remains steady. The large endo/lysosomal membrane protein (MP) Niemann-Pick C1 (NPC1), which is involved in cellular cholesterol transport, is a crucial intracellular receptor for viral infection. NPC1 is a ubiquitous housekeeping protein esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…Determining viral entry receptors is the principal determinant of host range and tissue tropism. Viruses also utilize cellular lipids and host lipid metabolism to facilitate reproduction and spread [ 85 ]. The host cell and the virus may both have perspectives on cholesterol during a viral infection.…”
Section: Pcsk9 Vaccines and Therapeutic In Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining viral entry receptors is the principal determinant of host range and tissue tropism. Viruses also utilize cellular lipids and host lipid metabolism to facilitate reproduction and spread [ 85 ]. The host cell and the virus may both have perspectives on cholesterol during a viral infection.…”
Section: Pcsk9 Vaccines and Therapeutic In Viral Infectionmentioning
confidence: 99%
“…Nonetheless, the researchers’ findings offer an initial indication of how to investigate this route further. By employing a stable replicon cell line and conducting time-of-addition experiments, it was determined that imipramine hindered the post-fusion viral RNA replication stages and prevented the entrance and/or fusion of retroviral pseudoparticles carrying the chikungunya virus envelope [ 85 88 ].…”
Section: Pcsk9 Vaccines and Therapeutic In Viral Infectionmentioning
confidence: 99%
“…Consistent with this, studies using cell lines derived from green monkey and human tissue showed a decrease in the ability of Ebola and Marburg viral analogs to infect cells with SNPs inserted into the NPC1 sequence ( Kondoh et al, 2018 ). Finally, several antiviral drugs work by blocking the NPC1 protein in patients ( Ahmad et al, 2023 ), suggesting that heterozygotes are likely to experience increased resistance to such infections.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, we described several key roles how cholesterol at the cell surface and in endolysosomes influences the efficacy of SARS-CoV-2 entry, providing opportunities for drugs targeting cholesterol-sensitive mechanism in these locations to reduce SARS-CoV-2 infectivity and COVID-19 disease severity. It would have gone beyond the scope of this review to cover the influence of cholesterol on many other aspects of the viral cycle, such as replication, assembly, and viral release, and we refer the reader to excellent review articles that cover cholesterol-sensitive mechanisms not only during SARS-CoV-2 surface recognition and cell entry but also viral replication, assembly, and release ( Ballout et al, 2020 ; Fecchi et al, 2020 ; Tang et al, 2021b ; Glitscher & Hildt, 2021 ; Palacios-Rapalo et al, 2021 ; Barrantes, 2022 ; Cesar-Silva et al, 2022 ; Kowalska et al, 2022 ; Wang et al, 2022 , 2023 ; Ahmad et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%